ANALISA PERKEMBANGAN MANAJEMEN SUMBER DAYA INSANI DALAM MEWUJUDKAN PEREKONOMIAN YANG STABIL - Jeni Devi Anjelina; Rania Salsabila; Dwi Ayu Fitriyanti; Nisak Dwi Lestari (Universitas KH. A. Wahab Hasbullah, 2021)
Abstract In writing this journal aims to find out about the influence of human resources in realizing a stable economy. Human resource management has a very large role in the process of improving or improving a poor economy. In realizing a stable economy, human performance is needed. Human resources have an important role, namely human performance will grow new innovations or new ideas that are very helpful in improving the economy. Keyword: SDI development, SDI planning in Islamic banking